Laboratorío de laboratorio de voip con equipos alcatel – lucent - Cantos Tejada, Jaime (2010)
The present project will allow to the students of PROTEL, besides having the concept of the subject, to assimilate it with the practice, for a better understanding of that studied, this laboratory will be focused to the technology Voice over IP that every time is coupled more to the managerial sector, this way the students will have the basic knowledge for a better labor acting. The project will take charge of providing the necessary teams for the operation of the same one, each one of these it is detailed in this manual with its functions, use, details technical and correct handling, the teams to use are of the mark Alcatel - Lucent. With this laboratory it is sought to demonstrate that the communication technologies every day they converge more toward the net Internet, to show the advantages and disadvantages of VoIP on the conventional telephony, to analyze the quality of service in the communications IP and to discover the procedure of installation of teams related with the transmission of a call on IP.